2008
DOI: 10.1103/physrevlett.100.016804
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Elastic Behavior of Nanocrystalline Diamond Thin Films

Abstract: This Letter studies the relationship between the elastic constants and the microstructure of nanocrystalline diamond thin films deposited by the chemical vapor deposition method doping various concentration of N2 gas. The elastic constants were measured by resonant ultrasound spectroscopy and picosecond laser ultrasounds. The increase of N2 gas decreases the diagonal elastic constants, but increases the off-diagonal elastic constants. The micromechanics calculation can explain this unusual elastic behavior, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 27 publications
3
28
0
Order By: Relevance
“…However, our results seem to be in general agreement with measurements of Tanei et al, 13,14 who found an increase of Poisson's ratio for decreasing grain size and an increasing sp 2 bonded carbon content.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…However, our results seem to be in general agreement with measurements of Tanei et al, 13,14 who found an increase of Poisson's ratio for decreasing grain size and an increasing sp 2 bonded carbon content.…”
Section: Resultssupporting
confidence: 93%
“…Brillouin light scattering measurements by Jiang et al 10 the gas phase of the hot filament CVD, while Poisson's ratio of nanocrystalline diamond was found to increase up to 0.18 after addition of 0.5% N 2 to the gas phase. 13,14 In a simple approach the Poisson's ratio can be measured by the change of the width of a beam during elongation. 15 This approach is relatively inaccurate; especially in the case where Poisson's ratio is small, such as for diamond.…”
mentioning
confidence: 99%
“…They are also sensitive to the presence of defects even when their volume fraction is small; they can be used to evaluate reliability of microstructures or nanostructures. 1,2 This paper studies the relationship between elastic moduli and microstructure of sputtered vitreous silica ͑v-SiO 2 ͒ thin films using picosecond ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…Macroscopically, it involves information on inclusions, 1-4 noncohesive grain bonds, 5 oriented heterogeneous phases, 6,7 and so on. In the case of defective inclusions, the stiffness decreases because the stress concentration around the defects causes larger deformation.…”
Section: Introductionmentioning
confidence: 99%